2011
DOI: 10.1111/j.1600-0846.2011.00533.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel anti‐wrinkle effect of cosmeceutical product with new retinyl retinoate microsphere using biodegradable polymer

Abstract: Retinyl retinoate has a potent anti-wrinkle activity, and the PLA-retinyl retinoate microsphere could be a useful cosmeceutical product for anti-aging purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
0
6
0
2
Order By: Relevance
“…Scanning electron microscope (SEM) image of PLA retinyl retinoate microspheres, mean diameter 12.87lm [60]. ment of the upper layers of the epidermis [65].…”
Section: Figure 12mentioning
confidence: 99%
See 2 more Smart Citations
“…Scanning electron microscope (SEM) image of PLA retinyl retinoate microspheres, mean diameter 12.87lm [60]. ment of the upper layers of the epidermis [65].…”
Section: Figure 12mentioning
confidence: 99%
“…In cosmetic applications, the use of PLA has been recently reported to encapsulate retinyl retinoate as an anti‐wrinkle treatment . Skin penetration studies revealed the PLA retinyl retinoate microspheres (Fig.…”
Section: Poly α‐Esters (Pga Pla Plga Pcl)mentioning
confidence: 99%
See 1 more Smart Citation
“…Egg album microspheres containing vitamin A were applied to prepare O/W creams, resulting in a prolonged release and higher bioavailability of that vitamin (Patavale and Mandawgade 2008). The use of polylactic acid has been recently reported to encapsulate retinyl retinoate as an antiwrinkle treatment (Kim et al 2012). Furthermore, the encapsulation and stabilization of ascorbic acid using poly(lactic-co-glycolic acid) (PLGA) nanoparticles, as well as PLGA microparticles to stabilize urea (used as moisturizing agent) and provide effective means of controlled release, has been described (Haddadi et al 2008).…”
Section: Encapsulating Structuresmentioning
confidence: 99%
“…Yaşlı derideki kırışıklıklar yüzeysel epidermiste olabildiği gibi, dermisteki kollajen veya elastin tahribatı nedeniyle de olabilmektedir 34 . Stratum corneum tabakasında bulunan intrasellüler lipitlerin cildin genç görünümünü sağlamadaki rolü büyüktür 10,19,35,36 . Yaşlanma karşıtı aktif bileşenler arasında; nemlendirici ve dolgunlaştırıcılar, hücre yenileyici ve onarıcılar, antioksidanlar, dermiste onarım sağlayan maddeler, kollajen sentezini uyararak deri elastikiyetini artıranlar ve fotoyaşlanmadan koruyanlar sayılabilir.…”
Section: Kollajen Ve Elastin Ile Bu Yapıları Destekleyen Bileşenlerunclassified